Newborn with Hereditary Sensory and Autonomic Neuropathy Type- IV: A Case Report (Bangladesh Journal of Child Health, 2022)
Hereditary sensory and autonomic neuropathy type IV (HSAN-IV) is a very rare autosomal recessive disorder characterized by anhidrosis, recurrent fever, insensitivity to pain and temperature, hypotonia, and developmental delay. The most frequent complications of this disease are self-mutilation, febrile seizure, stroke, corneal scarring, multiple fractures, burn, osteomyelitis and joint deformities. There is no definitive treatment for this condition. Early diagnosis can reduce disease complications and number of cases.BANGLADESH J CHILD HEALTH 2021; VOL 45 (2) : 111-115